Expression patterns of Oct4, Cdx2, Tead4, and Yap1 proteins during blastocyst formation in embryos of the marsupial, Monodelphis domestica Wagner. Issue 3 (23rd April 2013) - Morrison, J. T.; Bantilan, N. S.; Wang, V. N.; Nellett, K. M.; Cruz, Y. P.
SUMMARY The marsupial blastocyst forms in an entirely different manner from its eutherian counterpart, involving cell–zona rather than cell–cell adhesion during the 8‐ to‐16‐cell transition. While the eutherian blastocyst consists of a spherical trophoblast completely enveloping a pluripotent inner cell mass, or pluriblast, the marsupial blastocyst forms initially as a bowl‐shaped monolayer of cells lining the zona pellucida at the embryonic pole (ep). This monolayer contains a small patch of centrally positioned pluriblast cells edged with trophoblast cells that later coalesce at the abembryonic pole. Using immunocytochemistry, we examined the localization of the proteins Oct4, Cdx2, Tead4, Sox2, and Yap1 in opossum embryos to determine if their temporal expression pattern differed from that in the mouse, given the important differences in cell behavior preceding blastocyst formation in these mammals. Our results indicate that these proteins are expressed in similar temporal patterns despite the topological differences between mouse and opossum cleavage‐stage embryos and blastocysts. That the Hippo‐pathway protein Yap1 localized specifically around the approximately 128‐cell stage to opossum trophoblast nuclei but remained in the cytoplasm of pluriblast cells suggests that this transcriptional regulator participates in allocating cells to the trophoblast lineage, as it does in mouse. Interestingly, in both mouse and opossum embryos, expression of the pluripotency marker Oct4 persisted after Cdx2, which signals trophoblast specification, began to be expressed in trophoblast cells. This and the observation that Cdx2 is present in opossum embryos well before blastomere–zona adhesion even occurs suggests that the proteins studied may have other roles in early mammalian embryonic development.